Quantitative Analysis Of Emergency Medical Record Documents Based On Mirm Standard 13.1.1 Snars Issue 1 In Rsjd Dr. Arif Zainudin Surakarta - Nabilatul Fanny; Liss Dyah Dewi Arini; Oliva Virvizat Prasastin; Yogheswaran Gopalan; Meita Dwi Purwanri (Proceeding of International Conference on Science, Health, And Technology, 2021)
SNARS 1st Edition is the latest accreditation standard made by KARS. SNARS Edition 1 has assessment standards, one of which is the MIRM 13.1.1 standard. Based on the initial survey at RSJD Dr. Arif Zainudin Surakarta already has regulations on emergency medical record documents. This study aims to provide input and evaluation in improving the quality of health services in completing medical record documents. The research method used is descriptive research with a retrospective approach. The sample consisted of 97 documents of emergency medical records with a systematic random sampling technique. Collecting data by means of observation, interviews and documentation. Data processing includes collecting, editing, tabulating, presenting data and descriptive data analysis. The results of the research on the regulation of emergency medical record documents are 100% compiled in accordance with the regulations. Time of arrival and exit, there were 88 complete medical record documents or 88.65% and 11 incomplete emergency medical record documents or 11, 34%. Summary of conditions when discharged from the emergency service unit, there are 81 complete emergency medical record documents or 78.57% and 16 emergency medical record documents are incomplete or 15.52%. Instructions for follow-up care were 100% complete. Conclusion of quantitative analysis of emergency medical record documents based on the standard MIRM 13.1.1 SNARS Edition 1 in RSJD Dr. Arif Zainudin Surakarta, there are still 16 incomplete medical record documents on items of arrival and exit times and a summary of the condition when the patient left the emergency service unit. It is better if there is a need for socialization to all caregivers regarding the accuracy in recording the filling of medical records.